An Improved Bioluminescence Resonance Energy Transfer Strategy for Imaging Intracellular Events in Single Cells and Living Subjects - De, Abhijit (2007)
Bioluminescence resonance energy transfer (BRET) is currently used for monitoring various intracellular events, including protein-protein interactions, in normal and aberrant signal transduction pathways. However, the BRET vectors currently used lackadequate sensitivity for imaging events of interest from both single living cells and small living subjects. Taking advantage of the critical relationship of BRET efficiency and donor quantum efficiency, we report generation of a novel BRET vector by fusing a GFP(2) acceptor protein with a novel mutant Renilla luciferase donor selected for higher quantum yield. This new BRET vector shows an overall 5.5-fold improvement in the BRET ratio, thereby greatly enhancing the dynamic range of the BRET signal. This new BRET strategy provides a unique platform to assay protein functions from both single live cells and cells located deep within small living subjects. The imaging utility of the new BRET vector is shown by constructing a sensor using two mammalian target of rapamycin pathway proteins (FKBP12 and FRB) that dimerize only in the presence of rapamycin. This new BRET vector should facilitate high-throughput sensitive BRET assays, including studies in single live cells and small living subjects. Applications will include anticancer therapy screening in cell culture and in small living animals.